Tolerance for Postponing Elections in Crisis Conditions - Plutowski, Luke; Zechmeister, Elizabeth J. (Revista Latinoamericana de Opinión Pública, 2022)
Election postponements occur around the world for a variety of reasons, but they became especially widespread during the Covid-19 pandemic. Little is known how the public perceives and reacts to such democratic delays. To shed light on this topic, we included a question module in the 2021 AmericasBarometer about tolerance for alterations to democracy during periods of crisis. The data reveal that tolerance for election postponements is quite high. Further, through a wording experiment, we find that the public is more willing to accept such a delay during a health emergency vis-à-vis an alternative condition (widespread violence). We contextualize these findings by comparing them with attitudes about a more extreme anti-democratic disruption: a coup d’etat by security forces. Coups are significantly less popular than election postponements, especially during a health emergency. The results improve our understanding of public appetite for authoritarianism during periods of crisis.